Challenges and opportunities of Italian-qualified pharmacists relocated to work in Great Britain: A cross-sectional survey - Giuseppe Pasculli; Corrado Giua; Enrico Keber; Osvaldo Cancellu; Naoko Arakawa; Andrea Manfrin (Pharmacia)
Background: The Italian university system is actively revising the Master of Pharmacy (MPharm) curriculum to reflect post-COVID healthcare needs and a greater clinical focus. Understanding the challenges and opportunities faced by Italian pharmacists that relocated to Great Britain (GB) might provide valuable insights regarding the transferability of knowledge and skills obtained in the Italian pharmacy degree. Aim: The study aimed to capture the perceptions of Italian pharmacists practising in GB regarding the Italian pharmacy degree programme and to explore the challenges and opportunities they face in their new professional environment, ultimately to inform the Italian government and related stakeholders (Ministry of University and Research, MUR) about the need to update the Italian MPharm curriculum to make it more clinically relevant and aligned with international standards. Materials and methods: The authors developed a 50-item survey, pilot tested and reviewed for face and content validity by an expert panel. Participants’ characteristics, reasons for moving to GB, and data on their experience of practising as a pharmacist in Italy and GB were collected using Likert-type items and open- and closed-ended questions. Convenience sampling was used, and a sample power calculation was not deemed necessary. Statistical analysis involved descriptive analysis presenting frequencies and percentages for Likert-type and categorical items. Results: An estimated 281 pharmacists qualified in Italy are registered with the General Pharmaceutical Council in GB. Of these, 54 took part in the survey, resulting in a probable coverage of the sample population of 19.2%. Respondents pointed to the lack of job satisfaction and limited future perspectives as the main reasons to leave Italy (38.9% and 83.3%, respectively). Other reasons to relocate to GB were clinically focused job opportunities and better salaries (68.5% and 79.6%, respectively). Notably, almost two-thirds of the participants affirmed that Italian pharmacy degrees were insufficient to meet the requirements for practising as a pharmacist in GB. Conclusion: Different approaches to teaching clinical pharmacy and practical aspects seen in the pharmacy degree programmes in Italy and GB highlight a clear need for aligning the Italian pharmacy curriculum with the modern requirements of the pharmacy profession. Additionally, this alignment would facilitate the movement of Italian pharmacists into the GB healthcare system and beyond.